Lasting Relationships Out of Unwarranted Fear: The POW Camp at Lake Wabaunsee, Kansas 1944-1945 - Flynn, Jake; Rosendahl, Adam (Kansas State University, The Chapman Center for Rural Studies, 2011)
The fear held between German POWs at Lake Wabaunsee Kansas and the local population was quickly eroded through professional and casual interactions. Shared culture and mutual respect laid a strong foundation for unlikely relationships that often lasted a lifetime.
Jake Flynn and Adam Rosendahl, “Lasting Relationships Out of Unwarranted Fear: The POW Camp at Lake Wabaunsee, Kansas 1944-1945,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/224.
Keywords: Camp Number 5; Civilian Conservation Corps; Eskridge; German prisoner of war camp; National Youth Association; Wabaunsee County